Design and Implementation of a Customer Relationship Management System for Medium-Sized Digital Printing Enterprises - Wongkar, Noel Marcell Jonathan; Wirdayanti, Wirdayanti; Syahrullah, Syahrullah; Rinianty, Rinianty; Lapatta, Nouval Trezandy (JUSIFO : Jurnal Sistem Informasi, 2024)
This study investigates the design and implementation of a Customer Relationship Management (CRM) system specifically developed to address the operational challenges faced by medium-sized enterprises in the digital printing sector, with Rio Digital Printing as a case study. The research identifies key issues such as communication gaps and the lack of real-time order tracking, which negatively impact customer satisfaction. Employing a prototyping methodology, the system was iteratively refined with active user participation, ensuring alignment with stakeholder requirements. Key features include real-time order tracking, automated notifications, and a comprehensive interactive dashboard to support data-driven decision-making. The results demonstrate that the CRM system significantly enhances operational transparency, improves customer engagement, and fosters loyalty. This study contributes to the academic discourse by addressing the underexplored application of CRM systems in small and medium-sized enterprises, presenting a scalable framework for adaptation in similar industries. The findings also provide practical implications, advocating for digital transformation as a strategy to improve competitiveness in dynamic market environments.